Using HIT to Support Informal Caregivers of Cancer Patients at Home: a Needs Assessment - Al Awar, Zeina (Université d'Ottawa / University of Ottawa, 2016)
Introduction: This research investigated the requirements of an HIT solution that is usable and useful to informal caregivers of cancer patients on home palliative care. Methodology: A needs assessment method was used with an exploratory and a confirmatory stage. Eight semi-structured interviews and two focus groups were used for data collection. Qualitative content analysis was used to analyse caregiver experiences with both inductive and deductive coding. Results/Discussion: Expressed and unexpressed caregiver needs were extracted into four categories, Implementation, Presentation, Information, and Practical Caregiving, and used to create the application requirements. Five user personas were created based on caregiving intensity and the functional level of the patients, a method of tailoring the application content to the different personas was created, and a low-fidelity prototype of the application was designed. Conclusion: The findings of this research can improve the preparedness and coping of informal caregivers of cancer patients on home palliative care.
Keywords: Informal Caregiving; Family Caregiving; Caregiving; Home Care; Health Information Technology; Informational Needs; User Personas; User-Centered Design; Palliative Care; Needs Assessment; Cancer Care